(untitled) (Altre Modernità, 2025)
1848-49: in the months of the Revolution and the Republic Giuseppe Rovani is in Venice. After the fall of the city, following the route of many exiles, he found refuge in Capolago in Canton Ticino, at the Tipografia Elvetica, a centre for publishing and distributing the clandestine Risorgimento press. Also, in the light of some unpublished letters (a rare commodity in Rovani’s bibliography), both from family and non-family and addressed to him in the three-year period 1848-1850, the essay intends to add a piece to a biographical period that is still partially in the shadows.